Leon G. Bagley, Charter and Ordinances of the City of Rutland, Together with Extracts from Certain State Laws Applicable to the Affairs of the City. Also the Rules and Order of Business of the City Council and of the Board of Aldermen, and a Register of Municipal Officers, at 193, ch. 22, § 40 (1894) - (:unkn) unknown (General Publisher, 1894)
No person shall keep in any building or place within the city, excepting in such magazine or place of storage as may be provided by or under the direction of the city council, any greater quantity than twenty-five pounds of gunpowder, nitro-glycerine or other like compound for a longer period than twenty-four hours.
--
Keywords: GUN POWDER STORAGE